Political turnover and business decision: A study of Indonesian public companies - Dzakiyyah Saniyyah Rahmah; Yulianti Abbas (Journal of Accounting and Investment, 2023)
Research aims: This study aims to explore whether and to what extent political turnover (a change of local government head) is associated with a firm’s business decisions, such as tax avoidance and corporate investment.Design/Methodology/Approach: Using a sample of companies listed in the Indonesia Stock Exchange from 2012-2021, the authors measured the association between changes in local government leaders and business decisions using panel data regression with Driscoll & Kraay’s Standard Error. The authors hand-collected data on changes in local government leaders in 183 Indonesian cities to measure political turnover and merged the data with financial variables collected from the Eikon database.Research findings: This study uncovered that local political turnover in the region of companies' headquarters was negatively associated with tax avoidance decisions. This study also found that local political turnover negatively affected corporate investment decisions during normal/non-crisis periods. Consistent with the Resource Dependence Theory, the results of this study suggest that firms treat relationships with local government as an important resource. Political turnover thus creates uncertainty on the sustainability of the resources, causing firms to adjust their business decisions.Theoretical contribution/Originality: This study provides an understanding of how changes in political conditions in Indonesia change business strategy decisions. Besides, this research area is still under-studied in Indonesia.Research limitation: Since this study focused on the uncertainty caused by political turnover, this study did not measure firms’ political connections.